The politics of actually existing unsustainability human flourishing in a climate-changed, carbon-constrained world - Barry, John, 1966- (New York ; Oxford : Oxford University Press, 2012)
Going against both the naive techno-optimism of 'greening business as usual' and a resurgent 'catastrophism' within green thinking and politics, 'The Politics of Unsustainability' offers an analysis of the causes of unsustainability and diminished human flourishing.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Economic development; Economic security; Green movement